Prospective teachers’ creativity in constructing learning media in project brain-based learning (PjBBL) model - Ivayuni Listiani; Supri Wahyudi Utomo; Sugiarti; Erma Yulitasari (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2024)
Creativity is an essential competency for prospective teachers, especially in learning preparation. In learning, teachers’ creativity establishes an innovative learning process. However, the studies on prospective teachers’ creativity in developing learning media have not been carried out comprehensively. Therefore, this study investigates the prospective teachers’ creativity in constructing learning media using a descriptive qualitative approach. As many as 131 students from Universitas PGRI Madiun, Indonesia, participated in this study. The participants were asked to compose learning media at the end of the course. Besides they were also given 10 question items. Our results suggested the different levels of creativity among the prospective teachers attending learnings with PjBBL, PjBL, BBL, and conventional learning methods.